2006
DOI: 10.1897/06-022r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of four veterinary parasiticides on larvae of the dung beetle Aphodius constans in the laboratory

Abstract: The environmental risk assessment of veterinary pharmaceuticals for dung beetles is strongly hampered because no standardized test method is available so far. Therefore, a test with the temperate dung beetle species Aphodius constans was developed. The survival of beetle larvae was determined after exposure to four veterinary parasitical pharmaceuticals (ivermectin, moxidectin, dicyclanil, and praziquantel) representing different treatment regimes, modes of action, and effect levels. The test was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 23 publications
3
66
2
6
Order By: Relevance
“…This final LC 50 value was of the same order of magnitude as those obtained by Hempel et al [8] (LC 50 880-980 µg a.s. kg −1 dung (d.w.)) when ivermectin was spiked in dung, both using fresh dung as well as dried, grounded and re-wetted dung as the test substrate. Hempel et al [8] showed that the ratio of NOEC (No-Observed Effect Concentration) / LOEC (No-Observed Effect Level)-values for spiked ivermectin ranged from 320 to 800 for dried dung to 310-780 for fresh dung (in µg a.s. kg −1 dung (d.w.)). When considering the concentration of ivermectin in dung collected one day after the topical administration to animals (only for heifers No.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This final LC 50 value was of the same order of magnitude as those obtained by Hempel et al [8] (LC 50 880-980 µg a.s. kg −1 dung (d.w.)) when ivermectin was spiked in dung, both using fresh dung as well as dried, grounded and re-wetted dung as the test substrate. Hempel et al [8] showed that the ratio of NOEC (No-Observed Effect Concentration) / LOEC (No-Observed Effect Level)-values for spiked ivermectin ranged from 320 to 800 for dried dung to 310-780 for fresh dung (in µg a.s. kg −1 dung (d.w.)). When considering the concentration of ivermectin in dung collected one day after the topical administration to animals (only for heifers No.…”
Section: Discussionsupporting
confidence: 85%
“…I), the concentration in dung ranged from 90 to 130 µg a.s. kg −1 (d.w.) and was lower than the NOEC determined by Hempel et al [8]. At day 3, the values ranged from 830 to 1450 µg a.s. kg −1 (d.w.) and were higher than the effect values of the tests performed by Hempel et al [8] (LC 50 , NOEC and LOEC) and obtained in the present work (LC 50 ). At day 12, the concentration values (300-430 µg a.s. kg −1 dung (d.w.)) were close to NOEC but lower than the LC 50 values.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The boxes were incubated at 20±2°C until emergence of the imagos. This rearing method respects a standard procedure for the breeding of A. constans that has been elaborated for testing the effects of veterinary pharmaceuticals on this species (Hempel et al, 2006;Lumaret et al, 2007). Ten eggs were deposited in each box, and 10 boxes were used for each dung type: a total of 400 eggs were deposited on the different substrates, i.e.…”
Section: Materials and Methods Laboratory Rearing Of A Constansmentioning
confidence: 99%